SISTEM PENDUKUNG KEPUTUSAN UNTUK SELEKSI PENERIMA KARTU KELUARGA SEJAHTERA (KKS) MENGGUNAKAN ANALISIS DISKRIMINAN (Studi pada Kelurahan 1 Ulu Kecamatan Seberang Ulu 1 Palembang) - Didin Astriani P; Maya Amelia (UNIVERSITAS INDO GLOBAL MANDIRI)
Defining the objective of social protection programs and determining the criteria as poor societies often become complex issue. The dynamic of poverty data requires the existance of local policies through village/kelurahan consultation. The policy through that consultation is also become main power for selecting the recipient of prosperous family card, but in fact, the decision to determine the criteria of poor household usually does not refer to the criteria of poor family. Based on this case, the determination of poor family's criteria needs a good system to prevent mistakes and frauds that is done by certain people, the system is known as decision support system.Decision Support System which is designed in this study is a combination of technology and methodology that can be used to help making decision in determining the recipient candidate of Prosperous Family Card. One of the methods that can be used to determine the recipient candidate of Prorperous Family Card is discriminant analysis. Discriminant analysis is one of the statistical analysis techniques that has utility to classify object of several groups. The statistical model that is generated by discriminant analysis is in the form of grouping function, to ptedict and classify the household whether the group deservd to receive the Prosperous Family Card or not. After the result of grouping by using discriminant analysis, the application in the form of decision support systen is made for selecting the simple candidate of Prosperous Family Card, interesting, and easy to use.Keywords : Discriminant Analysis, Decision Support System, Prosperous Family Card